Klasyfikacja dokumentów tekstowych sporządzonych w języku polskim - Lula, Paweł (The Cluster Analysis of Polish Text Documents, 2005)
The main purpose of the paper is to study the process of cluster analysis of Polish text documents. We consider the influence of different factors (choice of methods of text representation, utilization of stop-list and stemming, conducting Latent Semantic Analysis and choice of clustering methods) on results of clustering procedure. At the final part of the paper on the basis of experiment results we formulate some recommendations for carrying out clustering analysis of Polish texts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 302-310